miR-17-5p and miR-19b-3p prevent osteoarthritis progression by targeting EZH2 - Li, Yong (Exp Ther Med, 2020)
Osteoarthritis (OA) is a joint disease caused by a variety of factors, including aging, obesity and trauma. MicroRNAs (miRNAs) have been reported to be crucial regulators during OA progression. The present study aimed to investigate the role of miR-17-5p and miR-19b-3p during OA development. Interleukin (IL)-1β-treated chondrocytes were used to mimic OA in vitro. The expression levels of miR-17-5p and enhancer of zeste homolog 2 (EZH2) were measured in cartilage tissues and chondrocytes using reverse transcription-quantitative PCR or western blotting. Apoptosis was assessed by flow cytometry. The protein expression levels of extracellular matrix (ECM)-associated genes were detected by western blotting. The binding sites between miR-17-5p or miR-19b-3p and EZH2 were predicted using the MicroT-CDS online database and verified using dual-luciferase reporter and RIP assays. miR-17-5p expression was downregulated, whereas EZH2 expression was upregulated in OA cartilage tissues and IL-1β-induced chondrocytes compared with that in the control tissues and cells. miR-17-5p mimics inhibited IL-1β-induced apoptosis and ECM degradation in chondrocytes. EZH2 was the target of miR-17-5p and miR-19b-3p in chondrocytes, and enhanced apoptosis and ECM degradation in IL-1β-stimulated chondrocytes. Rescue experiments revealed that miR-17-5p or miR-19b-3p mimic-induced inhibition of OA progression was reversed by EZH2 overexpression. In conclusion, miR-17-5p and miR-19b-3p inhibited OA progression by targeting EZH2, which may serve as a potential therapeutic target for OA.